2019
DOI: 10.1016/j.jfda.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A rapid LC-MS/MS method for simultaneous determination of quetiapine and duloxetine in rat plasma and its application to pharmacokinetic interaction study

Abstract: Combinations of new antidepressants like duloxetine and second-generation antipsychotics like quetiapine are used in clinical treatment of major depressive disorder, as well as in forensic toxicology scenarios. The drug–drug interaction (DDI) between quetiapine and duloxetine is worthy of attention to avoid unnecessary adverse effects. However, no pharmacokinetic DDI studies of quetiapine and duloxetine have been reported. In the present study, a rapid and sensitive liquid chromatography tandem mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Typically, the GC-MS method provided high sensitivity and accuracy, but according to the literature, all previous studies used time-consuming sample preparation, such as derivatization of the sample before determination, without determining the minimum concentration of quetiapine that can be determined under these conditions [28]. The proposed and used GC-MS method is characterized by relatively simple sample preparation, relatively short analysis time, the ability to detect the substance without the use of standard samples, due to the presence of large electronic libraries of mass spectra.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…Typically, the GC-MS method provided high sensitivity and accuracy, but according to the literature, all previous studies used time-consuming sample preparation, such as derivatization of the sample before determination, without determining the minimum concentration of quetiapine that can be determined under these conditions [28]. The proposed and used GC-MS method is characterized by relatively simple sample preparation, relatively short analysis time, the ability to detect the substance without the use of standard samples, due to the presence of large electronic libraries of mass spectra.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…An Xterra RP8 column (50 × 4.6 mm, 5 μm) and an isocratic mobile phase consisting of 30 mM ammonium formate (pH 5.0) and acetonitrile were used in the separation. The LLOD and LLOQ were 0.04 and 0.1 ng mL −1 , respectively (Reddy et al, 2012 (Chen et al, 2019).…”
Section: Chromatographic Methodsmentioning
confidence: 98%
“…The triple quadrupole MS was operated in positive ion ESI mode, and a multiple reaction monitoring mode was applied for the quantification. Pharmacokinetic interaction of quetiapine and duloxetine was studied; it was found that concomitant administration of both substances significantly increased plasma concentrations of DLX (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A good balance between simplicity and sensitivity for duloxetine determination was achieved by Chen et al (). Duloxetine rat plasma samples were treated by a one‐step protein precipitation method without drying or redissolving, thus greatly simplifying the sample preparation process.…”
Section: Techniquesmentioning
confidence: 99%